M. Tabrani Library Promotion Strategy Through Instagram and TikTok Platforms to Increase Reading Interest and Visitor Participation - Aminatut Taqiyah; Amsika Rahmawati; Anggita Febrianti; Rusdiana Navlia (Penerbit Presisi Pustaka, 2026)
Libraries in the digital era are required to adapt to technological developments and societal interaction patterns. Social media, particularly Instagram and TikTok, have become strategic tools to promote library services and collections. This study analyzes the promotional strategies implemented by M. Tabrani Library through these two platforms to increase reading interest and visitor participation. Using a descriptive qualitative approach, this study employs data triangulation through interviews, social media content analysis, and observation via social media accounts. The research results indicate that visually and interactively based promotional strategies on Instagram, as well as creative video-based strategies on TikTok, significantly attract audience attention, increase digital engagement, and impact the increase in library visit interest. Collaboration with various school institutions and trend-based content are key factors for success. This research is expected to strengthen the information service innovation model and become a practical reference for similar institutions in building a positive image and increasing local community literacy.